Refunctionalization of Religious Service Officials at the Makassar City Ministry of Religion Office - Siraj, Arifuddin (Jurnal Ilmiah Ilmu Administrasi Publik, 2018)
The purpose of the study is to describe the functionalization of religious service apparatuses at the Ministry of Religion Office in Makassar City. This type of research uses qualitative research with descriptive analysis. The research location was carried out at the Ministry of Religion of Makassar City. Data sources use primary data through in-depth interviews with various informants, namely: Head of the Makassar City Ministry of Religion, KUA, Religious Extension, da'wah da'wah, and religious leaders, people who are considered representative, those who are active and involved both directly and indirect in handling religious services. While secondary data document data from the Ministry of Religion office, the government is relevant to the research theme. The data analysis technique used in this study is a qualitative descriptive technique using an interactive phenomenological model by looking at the processes associated with the appropriation of the apparatus. The results of the study show that the re-functionalization of the apparatus in religious services is not maximized by the community. This can be seen from four things, such as: 1) Redesign of the Main Functions of Religious Servants, 2) Changes to the Paradigm of Religious Services, 3) Changes to Main Tasks and Functions of Religious Servants, and 4) Changes in Operational Standards for Religious Servants.